Deteksi Penggunaan Masker dan Klasifikasi Secara Real Time Melalui Video Webcam Dengan Metode YOLO - Saddhananda; Chairisni Lubis (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
The use of masks is currently important to prevent the spread of the virus. However, there are often people who do not wear masks in public places. Therefore, a real-time mask detection system is needed via webcam video. This system uses the You Only Look Once (YOLO) method to detect faces and classify whether the person is wearing a mask or not. The YOLO model is used to detect and classify masks in images and is trained using datasets from kaggle. The results for YOLO show the detection accuracy for masks is 92% using training data.